Does National Context Matter When Women Surpass Their Partner in Status? - Vink, Melissa; van der Lippe, Tanja; Derks, Belle; Ellemers, Naomi (Frontiers in Psychology, 2022)
There is growing evidence that couples in non-traditional relationships in which the woman attains higher status than her male partner experience more negative relationship outcomes than traditional couples. A possible reason is that non-traditional couples violate persisting gender stereotypes that prescribe men to be breadwinners and women to be caregivers of the family. In the current study (N = 2748), we investigated whether a country’s gender-stereotypical culture predicts non-traditional men and women’s relationship and life outcomes. We used the European Sustainable Workforce Survey, which is conducted in nine European countries. Two indicators of countries’ gender-stereotypical culture are used: Gender Empowerment Measure and implicit gender stereotypes. We found that women’s income and -to a lesser extent- education degree relative to their male partner affected outcomes such as relationship quality, negative emotions, and experienced time pressure. Furthermore, men and women living in countries with a traditional gender-stereotypical culture (e.g., The Netherlands, Hungary) reported lower relationship quality when women earned more than their partners. Relative income differences did not affect the relationship quality of participants living in egalitarian countries (e.g., Sweden, Finland). Also, couples in which the woman is more highly educated than the man reported higher relationship quality in egalitarian countries, but not in traditional countries. Our findings suggest that dominant beliefs and ideologies in society can hinder or facilitate couples in non-traditional relationships.